Interactive Radio Instruction: An Update from the Field - Bosch, Andrea; Rhodes, Rebecca; Kariuki, Sera (Education Development Center, 2002)
Interactive radio instruction (IRI), a methodology developed to turn a typically one-way technology into a tool for active learning in and outside the classroom, continues to be an attractive educational strategy in developing countries after almost 30 years. The original model for IRI math, created in Nicaragua by a team from Stanford University in the early 1970s, sought to combine the low cost and high reach of the radio medium and a clear understanding of how people learn. Since that time, 20 countries around the world have developed IRI programs for a variety of subjects, audiences, and learning environments, many of which have been sustained for up to 10 years and counting. The methodology has been expanded and adapted to include different levels of math, science, health, English, Spanish and Portuguese, environmental education, early childhood development, and adult basic education for learners of all ages. In each case, the series has been designed specifically by local specialists to be engaging and to meet learning objectives in that country. After three decades, interest in IRI does not seem to be waning. (See the Annex at the end of this chapter for a list of IRI projects and their current status.) This chapter updates earlier information about interactive radio instruction over the past five years, and introduces two cases where IRI has had an impact in Africa in two ways not captured in the past.1 In Guinea, IRI has gone to scale on an unprecedented level in West Africa to reach students and teachers on a national level. The Guinean IRI series is integrated with teacher development initiatives and is used in almost all primary schools across the nation, with 880,000 students. In Zambia, a new IRI series is being developed that reaches out to students who otherwise would be without schools, and have become increasingly vulnerable due to poverty and the HIV/AIDs. This example shows how IRI can be used effectively to overcome obstacles of access in Africa and to increase the chances that students can receive an education. These examples show how IRI retains its core elements, yet continues to evolve to meet new educational and social challenges.
KerkoCite.ItemAlsoKnownAs: 2339240:NJJTZUJS 2405685:PNRBAXJM

Developing an HIV/AIDS Education Curriculum for Takalani Sesame, South Africa's Sesame Street - Segal, Lauren; Cole, Charlotte Frances; Fuld, Janice (Early Education and Development, 2002)
The HIV/AIDS pandemic in South Africa has prompted a need for extensive efforts to educate citizens of all ages about the disease and ways of coping with its impact. This paper describes the process of developing an HIV/AIDS education curriculum for Takalani Sesame, an educational media project for young South African children. The process began with formative research with adults and children, and extensive discussions with HIV/AIDS health specialists. Guided by the research and advice from specialists, a team of educators developed a comprehensive curriculum that the Takalani Sesame production team will use to create HIV/AIDS education messages for television, radio and outreach materials for children ages 3-7 and the adults who care for them.
shortDOI: 10/fhjtsf KerkoCite.ItemAlsoKnownAs: 10.1207/s15566935eed1304_2 10/fhjtsf 2339240:VV58PTMZ 2339240:YD9NA82U 2405685:BSUIDDJH 2405685:BVB9XUXR 2405685:SDJSW8BC